Phase 1b/2 study of blinatumomab in Japanese adults with relapsed/refractory acute lymphoblastic leukemia. Issue 4 (11th February 2020) - Kiyoi, Hitoshi; Morris, Joan D.; Oh, Iekuni; Maeda, Yoshinobu; Minami, Hironobu; Miyamoto, Toshihiro; Sakura, Toru; Iida, Hiroatsu; Tuglus, Catherine A.; Chen, Yuqi; Dos Santos, Cedric; Kalabus, James; et al.
Abstract: Adult patients with relapsed/refractory (R/R) B‐precursor acute lymphoblastic leukemia (ALL) have a poor prognosis. Blinatumomab is a bispecific T‐cell engager (BiTE) immuno‐oncology therapy with dual specificity for CD19 and CD3 that redirects patients' CD3‐positive cytotoxic T cells to lyse malignant and normal B cells. We conducted an open‐label, phase 1b/2 study to determine the safety, pharmacokinetics, efficacy and recommended dose of blinatumomab in Japanese adults with R/R B‐precursor ALL. Patients received 9 μg/day blinatumomab during week 1 and 28 μg/day during weeks 2‐4, with a 2‐week treatment‐free interval (6‐week cycle); patients received 28 μg/day blinatumomab in subsequent cycles. Primary endpoints were the incidence of dose‐limiting toxicities (DLT) in phase 1b and complete remission (CR)/CR with partial hematologic recovery (CRh) within the first two cycles in phase 2. A total of 26 patients enrolled and 25 (96%) reported grade ≥3 adverse events (mostly cytopenias). There were no DLT. CR/CRh within two cycles was achieved by 4 of 5 patients (80%) in phase 1b and 8 of 21 patients (38%) in phase 2. Among patients with evaluable minimal residual disease, 4 (100%) in phase 1b and 3 (38%) in phase 2 had a complete MRD response. Median RFS for 8 patients who achieved CR/CRh in phase 2 was 5 (95% CI: 3.5‐6.4) months; median OS was not estimable. There were no significant associations between maximum cytokine levels or percentage of specific cell types during cycle 1 and response. Consistent with global studies, blinatumomab appeared to be safe and efficacious in Japanese adults with R/R ALL. Abstract : Flow of patients through the study. (A) Phase 1b part. (B) Phase 2 part.